Ethical rules and laws in demeaning education - HUSSB ATTI, SHAKIR; JAWAD KHUDEIR, HAMZA (Al-Adab Journal, 2021)
The degradation of education requires a set seif- imposed moral rules and positive laws that guarantee the educational institution ,and both of them follow one direction and goal , Researchers do not disagree that these moral laws stem from moral rules that are the product of society and that opinions differ about the precedence of morality over the law ,or vice versa ,or whether morals are absolute or limited ,or is it a acquired from the social environment or inherited , or does it have an obligatory characteristic, or does it give an area of freedom to the individual in some of its aspects, and the enactment of the reality of these propositions the answer to these question. The need for mixing between rules, laws and ethical behavior appeared in the evaluation and refinement the teaching profession, and what are the most important results that emerge in the event that these controls and standards are adhered to, and what are most important.